Mosques and Churches That Didn’t Exist Today and Used For Different Functions in Uşak - Aysim Börekcioğlu Dülgeroğlu; Mine Tanaç Zeren (Art-Sanat)
Uşak, which is located in the Central West Anatolian part of the Aegean Region and was a district of the Kütahya province until 1953, when it became a province; In the process from ancient times to the present, it has remained in the settlement area of many civilizations. Within the scope of this study, in which the religious buildings that were built in the historical process in the city and could not survive due to various reasons or were included in the present day with a different function, the Tuz Pazarı Mosque, Buğdaylı Mosque, Çallı Ömer Efendi Mosque and Nebi Mosque, as well as the St. Konstantinos-Eleni Church, Panayia Church, St. Marie De Dieu Church, were examined and the place and importance of the buildings in their periods were determined. In addition, Kırık Minare Mosque, which is used with a different function today, is also discussed within the scope of the study. Regarding the religious structures examined; In addition to data about the dates of construction, their location in the city and their extinction process, many photographs were also obtained. In addition, all these historical data were analyzed and the architectural features of the structures unearthed were tried to be read. While there is a lot of information in the sources about the monumental mosque structures and churches, on a smaller scale; Structures such as masjid, tomb, dervish lodge and zaviye are only mentioned in the sources. In addition to the natural disasters and deliberate destructions experienced in different periods, local governments also have a great impact on the physical structure of the city of Uşak. This study, which aims to make known the religious structures that have not survived in the city, is also very important in terms of revealing the reasons for the disappearance of these values that the city lost.